The Speed of Injury and Its Concussion Among Some Basic Skills for Youth Football - Al-Enezi, Noura Amer Aliwi (Indonesian Journal Publisher, 2024)
The current research aimed to identify the speed of motor response to some basic skills in youth soccer players, and to identify the relationship between some basic skills and the speed of motor response in youth soccer players. The descriptive method was used by the researcher in the form of correlations to fit the research question. The research community was represented by young football players of the Border Sports Club in football, and the number of players (26) players were selected by the random method, and the researcher chose the research sample by random method and consisted of (18) players, the goalkeepers were excluded from the lottery and their number (3) and the sample was excluded from the exploratory experiment and their number (5). The speed of reaction test and the basic skills test were determined after being presented to a group of experts and specialists who considered it one of the most important basic skills in the game of football, as most scientific sources emphasize that it is the basis of the learning and training process in the game of football. And because mastering this skill will quickly help improve the performance of other skills. The researcher relied on the statistical package (SPSS) version (25). The researcher concluded from her study that young soccer players are characterized by fast motor response, and that the speed of motor response has an effective role in the accuracy of some special skills, including the skill of handling, rolling and shooting for young soccer players.